Driving Financial Accountability through ISAK 35 - Baiq Krisnina Maharani Putri; Fety Widianti Aptasari; Khairul Mujahidi; Ely Windarti Hastuti (Westscience Press, 2026)
Objectives – This study aims to examine and gain a deeper understanding of the implementation of ISAK 35 in Islamic boarding schools, as well as to explore stakeholders’ perspectives on the existing accountability practices within Islamic boarding schools. Research Methods – This study employs a qualitative research method using a case study approach at one of the major Islamic boarding schools on Lombok Island, Indonesia. Data were collected through interviews, observations, and documentation. Findings – The findings of this study indicate that the Islamic boarding school has not fully recognized and implemented ISAK 35 in its financial reporting practices. The accountability practices applied by the Islamic boarding school are carried out based on the values, traditions, and management system upheld within the institution. Financial accountability is also adjusted to the needs and expectations of its stakeholders. Although stakeholders generally perceive the current accountability practices as adequate, there are still expectations for future improvements, particularly in terms of more systematic financial record-keeping and the adoption of more formal financial reporting standards such as ISAK 35. Originality – This study not only examines the implementation of ISAK 35 and the accountability practices within the Islamic boarding school, but also explores stakeholders’ perspectives regarding the current accountability practices and the type of accountability system they expect to be implemented in the future.